PHILOSOPHICAL-HERMENEVIC APPROACH TO THE STUDY OF THE CATEGORY OF INTERCULTURAL COMMUNICATION (Scientific journal of the Fergana State University, 2023)
This article explains the historical development of tourism in the world and the importance of intercultural communication in these processes. The processes that make the Asia-Pacific region an important element of international tourism are analyzed. Particular attention will also be paid to the analysis of the causes and prospects of the development of tourism potential in these regions.